STUDI SOSIOLOGIS ATAS KASUS-KASUS HUKUM YANG VIRAL (NO VIRAL, NO JUSTICE) - Elva Feria Sondari (JOSH: Journal of Sharia, 2026)
The "No Viral, No Justice" phenomenon reflects the dependence of law enforcement in Indonesia on social media pressure, which increases accountability yet risks undermining judicial objectivity. This qualitative research, employing a legal sociology approach, utilizes documentation studies and digital observations of literature and social media narratives to analyze the interaction between public opinion and the institutional responses of law enforcement agencies through interactive model data analysis techniques. Sociologically, the "No Viral, No Justice" phenomenon and the practice of trial by social media serve as digital social control instruments that enhance transparency and official accountability; however, juridically, they pose a risk to judicial objectivity and individual rights. Therefore, a balance between public oversight and adherence to formal legal procedures is essential to ensure that justice does not become ensnared in emotional digital populism.